Childcraft Our World 6 - "World Book" (World Book International : World Book: London, 1996)
Illustrated articles, stories, and poems, grouped thematically in fifteen volumes under titles including "World and space, ""About animals, ""How things work," and "Make and do."
Keywords: Children's encyclopedias and dictionaries